2015
DOI: 10.1186/s12917-015-0555-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of 3 % hypertonic saline and 20 % mannitol on canine whole blood coagulation and platelet function

Abstract: BackgroundHyperosmolar therapy, using either mannitol or hypertonic saline (HTS), is considered the treatment of choice for intracranial hypertension. However, hyperosmolar agents may impair coagulation and platelet function, limiting their use in patients at risk for hemorrhage. Despite this, studies evaluating the effects of mannitol compared to other hyperosmolar agents in dogs are largely lacking. The aim of this study was to compare the in vitro effects on global hemostasis and platelet function of 20 % m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
3
17
1
Order By: Relevance
“…we cannot exclude a dilutional or hypocoaguable effect seen with colloids and hypertonic saline. However, doses were lower than those administered in studies that showed significant effect on ROTEM parameters compared to dilution alone (Adamik, et al, 2015;Reuteler et al, 2017). As described above, tissue trauma in combination with hypoperfusion are the main causes for developing ATC.…”
Section: Discussionmentioning
confidence: 96%
“…we cannot exclude a dilutional or hypocoaguable effect seen with colloids and hypertonic saline. However, doses were lower than those administered in studies that showed significant effect on ROTEM parameters compared to dilution alone (Adamik, et al, 2015;Reuteler et al, 2017). As described above, tissue trauma in combination with hypoperfusion are the main causes for developing ATC.…”
Section: Discussionmentioning
confidence: 96%
“…In vitro administration of high dosages of hypertonic saline in people and dogs may be associated with coagulopathy due to platelet dysfunction, diminished clot propagation and clot strength, as well as impaired fibrin formation. 39,40 However, recent clinical studies in dogs do not report a hypocoagulable effect on ROTEM parameters after a single bolus of 7.2% hypertonic saline. 41 Fluid administration may further lead to dilutional coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous canine in vitro study, we expected that mannitol would have a greater impact on coagulation than HTS [17]. A second aim was to compare plasma osmolarity after either osmotherapeutic solution.…”
Section: Introductionmentioning
confidence: 99%